Intersemiotic Modernism: Matija Ferlin’s Sad Sam Lucky between Poetry and Its Embodiment - Rafolt, Leo (Przekłady Literatur Słowiańskich, 2023)
Sad Sam Lucky is a solo performance by the choreographer and performer Matija Ferlin, conceived as part of his ongoing non-dance-like and non-theatrelike conceptual project Sad Sam, which started in January 2004 in Amsterdam, where the first part of this pseudo-durational piece was premiered. Ferlin’s performance Sad Sam Lucky is somewhat specific in the author’s oeuvre, mainly because it assays to become a physical response to the work of the Slovenian avant-garde poet Srečko Kosovel (1904—1926), translating it and transposing it at the same time, in-between languages and dialects (Slovenian, Croatian, Istrian, and/or English), and in-between performative regimes (embodied response and a pseudo-recital). Kosovel’s confessional poetry, i.e. profound, contemporary, tense in its stylistic imagery, and, at the same time, almost revolutionary in its ideas, is therefore being performed as a live matter of language, driven by Ferlin’s main idea — not to do theatre, not to do dance, not to translate, but to trans-body Kosovel’s verses, and his melancholic prophecy, thus creating a form of a highly physical, turbulent and emotional homage to this very unique avant-garde author.